REVIEW OF SOLUTIONS FOR IMPROVING AUTHENTICATION AND AUTHORIZATION PROCESSES ON WEB RESOURCES - Коробейнікова, Тетяна; Непийвода, Максим; Матвійчук, Андрій (SWorldJournal, 2024)
The paper examines the analysis of the key concepts of authentication and authorization on web resources, demonstrating their necessity and application on web platforms. Various methods and means of protection are analyzed, including login and password,